Raven rise [compact disc, unabridged] - MacHale, D. J. (MacHale, D. J. Pendragon, 2008)
D.J. MacHale returns with the ninth book in his Pendragon series. The battle for Halla - all of existence - is set to begin, and Bobby Pendragon is missing. Mark and Countney do what they can to keep Second Earth from falling into the hands of Saint Dane, but resistance is faltering.